THE EFFECTIVENESS OF EDUCATION THROUGH VIDEO MEDIA ON THE KNOWLEDGE, ATTITUDES, AND BEHAVIOR OF HYPERTENSION PATIENTS IN THE WORKING AREA OF THE PALEMBANG CITY HEALTH CENTER - Racellyta, Dwinisa Dea; Intan Kumalasari; Faiza Yuniati (Perhimpunan Ahli Epidemiologi Indonesia, 2025)
Background: Hypertension is a non-communicable disease often referred to as the